2022
DOI: 10.3389/fonc.2022.949332
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of Chinese herbal medicine compounds and their nano-formulations on regulating the immune system microenvironment

Abstract: Traditional Chinese medicine (TCM), including herbal medicine, acupuncture and meditation, has a wide range of applications in China. In recent years, herbal compounding and active ingredients have been used to control tumor growth, reduce suffering, improve quality of life, and prolong the life span of cancer patients. To reduce side effects, herbal medicine can be used in conjunction with radiotherapy and chemotherapy or can be used as an adjuvant to strengthen the immune effect of anticancer vaccines. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 103 publications
0
12
0
1
Order By: Relevance
“…Several studies have shown that compounds such as emodin, anemoside A3, dihydroartemisinin, dihydroisotanshinone I, gastrodin, puerarin, ginkgolide B, salidroside, etc. that are present in different herbs used in traditional Chinese medicine have been shown to modulate immune cell responses in different cancer models both in vitro and in vivo [ 151 ].…”
Section: Recent Developments In Cancer Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that compounds such as emodin, anemoside A3, dihydroartemisinin, dihydroisotanshinone I, gastrodin, puerarin, ginkgolide B, salidroside, etc. that are present in different herbs used in traditional Chinese medicine have been shown to modulate immune cell responses in different cancer models both in vitro and in vivo [ 151 ].…”
Section: Recent Developments In Cancer Immunotherapymentioning
confidence: 99%
“…Similarly, herbal formulations such as Biejiajian pill, Yupingfeng, Baiying extract, Shuangshen granules, Xiaoyaosan, Yi-yi-fu-zi-bai-jiang-san, etc. have also shown promising immunomodulatory effects that could be harnessed for cancer immunotherapy [ 151 ]. To overcome bioavailability and targeting issues, nanoparticle mediated delivery of these phytocompounds have also been attempted.…”
Section: Recent Developments In Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Hinweise für direkte Antitumorwirkungen einzelner Arzneipflanzen finden sich immer wieder, überwiegend aus In-vitro-Studien und aus Tierversuchen [49]. Klinische Studien belegen bislang keine ausreichende Evidenz für den Einsatz von chinesischen Arzneipflanzen als Tumortherapie.…”
Section: Chinesische Arzneimittel Könnenunclassified
“…Worldwide, tumor is the first‐line cause of human deaths and produces serious financial constraint (Wu et al, 2019). The immune system of each individual is correlated with tumor development, and recently it has been revealed that herbal compounds with their active ingredients have been used to control tumor growth, improve quality of life, reduce suffering, and prolong the life span of cancer patients (Sun et al, 2022). For that reason, natural products have become the research focus as they have low toxicity, are reliable to use, and are easy to extract as they are generally available (Pratheeshkumar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%